Prevalence of bovine hepatic linguatuliasis in a slaughterhouse in Talca, Chile - Carrillo Parraguez, Miguel (2017)
The aim of this study was to determine the prevalence of hepatic linguatuliasis of cattle slaughtered in an abattoir in Talca, Chile. Livers (n=376) were examined and compatible lesions and the presence of the nymph of Linguatula serrata were recorded. The results showed that 13.8% of livers showed lesions compatible with linguatulosis and the etiologic diagnosis was obtained in 48% of them. No significant differences by age group (p=0.187) were found. In 28% of livers with etiologic diagnosis, linguatuliasis was the only parasitic disease, 60% was associated with liver fluke and in one case with one hydatid cyst. The prevalence of hepatic linguatuliasis was 6.7% based on the presence of L. serrata nymphs.